Několik úvah o české historiografii po roce 1989: Remarks on Czech historiography since 1989 - Górny, Maciej (Dějiny – teorie – kritika, 2007)
The article presents the state of historical research in Czechoslovakia (Czech Republic) since 1989 in comparative regional perspective. The first part of the text discusses the phenomenon of relatively delayed Czech debate on the impact of communist regime on historiography. The author of the summarized article is of the opinion that that due to this chronological shift the Czech historiography enjoys more sophisticated and developed methodological debates than analogical discussions led by Polish, German and Slovak historians in early 1990s. Second part of the article is devoted to the main research topics of contemporary Czech historiography, starting from the hussite movement, through the national awakening to the problem of expulsion of the German population of Czechoslovakia in 1945. The author’s stance is that the recent critical voices towards the traditional interpretation of an immanently democratic, peaceful and unique character of the interwar Czechoslovakia are in a way more convincingly proving the democratic and professional quality of the present Czech historical science than the ‘patriotic’ defence of the national values.